2009
DOI: 10.1209/0295-5075/87/37002
|View full text |Cite
|
Sign up to set email alerts
|

Anderson transition in disordered graphene

Abstract: In a recent comment by Schleede and coworkers [1], they have correctly pointed out presence of small negative spectral weights of the order 10 −4 in RKPM expansion of the Dirac delta function. However, we found that these negative values are not responsible for the vanishing of the typical density of states (DOS) near the charge neutrality point.To clarify this point, in Fig. 1 we have plotted a Dirac delta function with Jackson attenuation factors (Solid line), and with RKPM (dashed line). The Gibbs oscillati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 50 publications
6
54
2
Order By: Relevance
“…However, since the position of H adsorbates is random (see supplementary information), the question of the localization of impurity band states arises. To answer this question, we use the KPM method to calculate the typical electron density of states, wherein the vanishing of this DOS indicates localization 16 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since the position of H adsorbates is random (see supplementary information), the question of the localization of impurity band states arises. To answer this question, we use the KPM method to calculate the typical electron density of states, wherein the vanishing of this DOS indicates localization 16 . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the H impurity concentration is comparable to η c , in addition to the energy-dependent random potential (Anderson type), the hydrogenic wave functions will have substantial overlap to give rise to an impurity band. Moreover, for moderate values of the diagonal on-site disorder W ≈ γ, where W is the range of the on-site energies and γ is the C-C hopping energy, a mobility edge emerges in the conduction and valence bands 16 . The acceptor band survives the randomness regarding the position of the H atoms, and the states in the center of the acceptor band remain extended and a localization of these states is not expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent letter [1], Amini et al claim having found a mobility edge in graphene, a truly two-dimensional (2D) system. Their mobility edge ought to be induced by onsite uncorrelated (Anderson-type) disorder and-unlike to 3D systems-shall separate localized states in the band center, from the remaining extended states.…”
mentioning
confidence: 99%
“…When the disorder is introduced within the Anderson model, both atomic scale oscillations and the Friedel oscillations due to Fermi surface survive [8]. Note that the Dirac picture remains quire robust against the weak disorder [9]. Therefore given the dimensional consistency the overall physics of the RKKY interaction is expected to survive in weak disorders considered in [8].…”
Section: The Fate Of Fermi-surface Oscillationsmentioning
confidence: 99%